Tamarind techniques for fine art lithography - Devon, Marjorie
?Tamarind has been an informed energy, not an institution: an active expression of a yearning for creative freedom and excellence. June Wayne, founder. Eagerly awaited by artists and fine art printers everywhere, this comprehensive, all-new book created by the director and staff of the Tamarind Institute of Lithography at the University of New Mexico, Albuquerque, covers all facets of fine art lithography, from setting up a workshop of any size to pulling a successful edition. It offers complete, illustrated step by step instructions for all techniques in use today; up to date health and safety information; and full-color plates of over forty years? worth of lithographs created at Tamarind. Unrivaled in scope, this extraordinary manual will be an invaluable reference for students of the medium and a treasured resource in lithography workshops around the world for years to come